Genetic diversity of Bursaphelenchus cocophilus in South America - Silva, Arinaldo P.; Parra, Pedro P.; Campos, Vicente P.; Costa, Sara S.; Vicente, Cláudia S.L.; Ferreira, Letícia G.; Souza, Ricardo M.; Mota, Manuel (Brill, 2016)
Molecular characterisation ofBursaphelenchus cocophilus, the causal agent of ‘red ring disease’, is imperative for efficient identification procedures in Brazil and Colombia, because quarantine species such asB. xylophilusandB. mucronatusare already listed in both countries. ITS-1/2 region and D2-D3 segment of LSU rDNA were used to characterise isolates ofB. cocophilusobtained from coconut plantations in Brazil and Colombia. Results from ITS-1/2 and LSU rDNA regions showed that all isolates ofB. cocophilusfrom Brazil and Colombia formed a monophyletic group. The LSU rDNA region indicated that all isolates formed a single monophyletic group with high Bayesian posterior probability (100%). This is the first study on ITS-1/2 for the characterisation ofB. cocophiluspopulations. A species-specific primer was designed for identification ofB. cocophilus.